Students' Perception of the Implementation of Ki Hajar Dewantara Values in Strengthening Character Education at an Indonesian Senior High School - Ratu Rahmini; Rhoma Dwi Aria Yuliantri (Sakura Digital Nusantara, 2026)
This research is motivated by the limited study that focuses on students' perception directly of the implementation of Ki Hajar Dewantara's values in strengthening character education, especially at the high school level. This study is anchored in Ki Hajar Dewantara's educational trilogy as its theoretical foundation. This study aims to describe students' perceptions of the implementation of Ki Hajar Dewantara's values in strengthening character education at SMA Negeri 10 Berau. A convergent mixed-methods design, combining a Likert-scale questionnaire with semi-structured interviews, was used in this study. Data were collected through questionnaires of all 26 students of class X-B and semi-structured interviews with seven selected students. The results of the study showed that student perception was in the good category with an average overall score of 81.2%. The highest indicator was the role of teachers as motivators (Ing Madya Mangun Karso) at 82.5%, while the lowest indicator was the teacher's role model (Ing Ngarso Sung Tulodo) at 79.8%. This gap indicates that the exemplary aspect needs to be strengthened through a more structured teacher professional development program. Interview data confirmed that students felt motivated, valued as unique individuals, and experienced positive character development, especially in discipline, responsibility, and cooperation. This study recommends that school leaders and teacher professional development units design structured exemplary-modeling programs for teachers and strengthen the synergy of the Tri Education Center (family, school, and community) to support more holistic student character formation.